Status and Prospects of the Transfer of Forest Functions to Regional Governments - Zamora Velazco, Giuliana Nathalie (2021)
The process of the transfer of forestry functions, which began in 2009, was not completed; 15 Regional Governments have yet to assume the functions of monitoring and control; as well as administration and control of the forestry and wildlife resource (RFFS acronym in Spanish), provided for in the Organic Law of Regional Government (Article 51°). This situation is due to weaknesses inherent in the decentralization process at the national level, coupled with the weak leadership of SERFOR to lead the decentralization process and promote the decentralized management of RFFS, and, to the little interest of the Regional Governments in assuming these functions. This led an unclear and changing organization, weak operational capacity and capacity-building; among other problems, which have always affected the forest sector; this is the case with deforestation and corruption associated with harvesting. In addition, a case study is presented from the perspective of four departments; two of them, Cajamarca and Cusco, in which the transfer of forestry functions has not yet been carried out, and an administration dependent on SERFOR is maintained through an Technical Forest and Wildlife Administrations (ATFFS acronym in Spanish). The remaining two, Loreto and Ucayali, where the transfer of forestry functions took place, are managed in a decentralized manner through an ARFFS. As a result, it was evident that both types of administration have weaknesses. In the case of the ATFFS, they have weaknesses that lie in the little interest of SERFOR in strengthening its management, they have a low budget, incipient participation in the budget for results and investment projects that SERFOR executes. The Regional Forest and Wildlife Authority (ARFFS acronym in Spanish) have weaknesses related to the limited financial resources allocated by the Regional Governments in the administration of RFFS and the limited implementation of investment projects.